Monitoring wound healing in minor burns-A novel approach - Kenworthy, P.; Phillips, M.; Grisbrook, Tiffany; Gibson, W.; Wood, F.; Edgar, D. (Pergamon Press, 2017)
Assessment of minor burn wound closure is predominately determined by visual inspection and clinical specialist assessment, which remains largely a subjective analysis and results may vary depending on the clinician's experience. Bioimpedance spectroscopy (BIS) is an instrument that has a demonstrated ability to objectively monitor the wound healing process in various patient populations but has not yet been used in acute burn wounds.The aim of the pilot study was to examine whether the BIS technique is a valid measure of wound healing.Localised BIS resistance and phase angle triplicate measures, of minor limb burns, were collected on two serial occasions. Circumference limb measures were taken at the localised burn site to determine a truncated limb volume. Proportional-odds ordered logistic regression analyses determined resistance at zero frequency (R 0 , indicative of edema) and resistance of total body fluid (R inf ) were significantly associated with healing after adjustment for the influence of surgery. A one unit increase in R 0 and R inf increased the odds of wound healing by 6% and 5% respectively (p < 0.01). Phase angle at 50kHz and R i were not significantly associated with the markers of the wound healing process. Spearman's correlation determined there was a significant association between a healing wound and limb segment volume (ml) (rho -0.30, p < 0.01). BIS is a technique, which has the potential to monitor the progress of wound healing.